Association between human leukocyte antigen and immunosuppressive treatment outcomes in Chinese patients with aplastic anemia - Chen, Lingyun; Ge, Meili; Huo, Jiali; Ren, Xiang; Shao, Yingqi; Li, Xingxin; Huang, Jinbo; Wang, Min; Nie, Neng; Zhang, Jing; Peng, Jin; Zheng, Yizhou (Frontiers in Immunology, 2023)
Activated cytotoxic T cells (CTLs) recognize the auto-antigens presented on hematopoietic stem/progenitor cells (HSPCs) through class I human leukocyte antigen (HLA) molecules and play an important role in the immune pathogenesis of aplastic anemia (AA). Previous reports demonstrated that HLA was related to the disease susceptibility and response to immunosuppressive therapy (IST) in AA patients. Recent studies have indicated that specific HLA allele deletions, which helped AA patients to evade CTL-driven autoimmune responses and escape from immune surveillance, may lead to high-risk clonal evolution. Therefore, HLA genotyping has a particular predictive value for the response to IST and the risk of clonal evolution. However, there are limited studies on this topic in the Chinese population. To explore the value of HLA genotyping in Chinese patients with AA, 95 AA patients treated with IST were retrospectively investigated. Results showed that the alleles HLA-B*15:18 and HLA-C*04:01 were associated with a superior long-term response to IST (P = 0.025; P = 0.027, respectively), while the allele HLA-B*40:01 indicated an inferior result (P = 0.02). The allele HLA-A*01:01 and HLA-B*54:01 were associated with high-risk clonal evolution (P = 0.032; P = 0.01, respectively), and the former had a higher frequency in very severe AA (VSAA) patients than that in severe AA (SAA) patients (12.7% vs 0%, P = 0.02). The HLA-DQ*03:03 and HLA-DR*09:01 alleles were associated with high-risk clonal evolution and poor long-term survival in patients aged ≥40 years. Such patients may be recommended for early allogeneic hematopoietic stem cell transplantation rather than the routine IST treatment. In conclusion, HLA genotype has crucial value in predicting the outcome of IST and long-term survival in AA patients, and thus may assist an individualized treatment strategy.